2020
DOI: 10.1038/s41598-020-66713-3
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus reactivation in sepsis due to community-acquired pneumonia is associated with increased morbidity and an immunosuppressed host transcriptomic endotype

Abstract: there was a 24% incidence of EBV reactivation. Six individuals showed simultaneous reactivation of EBV and a second virus. Plasma sampling was enriched for earlier time points (Day 1 = 302; Day 3 = 284; Day 5 = 171).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…Additionally, high early TTV viraemia was associated with immune alteration. Single viraemia was more frequent than viraemia from multiple viruses, as previously observed using metagenomic sequencing (16), and the percentage of ICU patients who had at least one Herpesviridae-related viraemia increased over time, as noted by others (9,13). Our study adds to the literature evaluating herpesviruses reactivation in patients with critically ill conditions including sepsis summarised in Table 5.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Additionally, high early TTV viraemia was associated with immune alteration. Single viraemia was more frequent than viraemia from multiple viruses, as previously observed using metagenomic sequencing (16), and the percentage of ICU patients who had at least one Herpesviridae-related viraemia increased over time, as noted by others (9,13). Our study adds to the literature evaluating herpesviruses reactivation in patients with critically ill conditions including sepsis summarised in Table 5.…”
Section: Discussionsupporting
confidence: 80%
“…It is worth noting that individuals who went on to develop EBV reactivation appeared to present with more severe immune alteration. Consistent with these results, it was recently shown that EBV reactivation in sepsis was correlated with the SRS1 immunocompromised sepsis transcriptomic endotype ( 16 ). During the first week, TTV DNAemia appeared specifically associated with modulation of the lymphoid compartment, including decreased T cells and high expression of IL15 associated with high TTV titre.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In a multivariate model considering PtP's cytokines and chemokines as well as viral miRNAs on the day of injury, EBV and KSHV miRNAs were independently predictive of CR. Growing evidence suggests that both KSHV and EBV have the potential to reactivate from latency during times of stress (9,11,14,15,31,32). The high occurrence of patients with detectable miR-BHRF-1 in this study's PtPs and HCs is expected given that EBV infection is ubiquitous (33).…”
Section: Discussionmentioning
confidence: 74%